Sasanquasaponin inhibited epithelial to mesenchymal transition in prostate cancer by regulating the PI3K/Akt/mTOR and Smad pathways - Wenfeng Li; Yuanshen Mao; Bao Hua; Xin Gu; Chao Lu; Bin Xu; Weixin Pan (Taylor & Francis Group, 2022)
Context Sasanquasaponin (SQS) is a commonly used traditional Chinese medicine proved to have a wide range of pharmacological functions.Objective The objective of this study is to explore the effect and underlying mechanism of SQS in the treatment of prostate cancer (PC).Materials and methods PC cell lines (22Rv1 and PC-3) were treated with SQS (0, 0.5, 1, 2, and 4 μM) for 12 or 24 h. The viability of cells was evaluated, while the mRNA and protein levels of epithelial to mesenchymal transition (EMT)-related genes in PC cell lines were measured (Groups: Control, TGF-β1, TNF-α, TGF-β1 + TNF-α, and TGF-β1 + TNF-α + SQS). The migration and invasion abilities of PC cell lines were evaluated (Groups: Control, SQS). Finally, the antitumour effect of SQS (25, 50,100, and 200 mg/kg) in BALB/c nude mice (6 weeks, 18-20 g) was evaluated (Groups: Control, Vehicle, 25, 50,100, and 200 mg/kg SQS). The study duration was 1 month.Results SQS inhibited the viability and the number of colonies of 22Rv1 or PC-3 cells. The IC50 of SQS of 12 and 24 h in these two cells was 3.25, 1.82, 4.76, and 4.70 μM, respectively. SQS inhibited the adhesion, migration, and invasion of PC cells. It also inhibited the expression of EMT-related markers of PC cells. The PI3K/Akt/mTOR and Smad2/3 signalling pathways were activated in the process of EMT, and SQS could significantly reduce the activation of the PI3K/Akt/mTOR and Smad2/3 pathways. Finally, SQS inhibited the growth of xenograft tumours in vivo.Conclusions SQS inhibited EMT in PC by regulating the PI3K/Akt/mTOR and Smad pathways.